2012
DOI: 10.2166/wst.2012.033
|View full text |Cite
|
Sign up to set email alerts
|

Implications to stormwater management as a result of lot scale rainwater tank systems: a case study in Western Sydney, Australia

Abstract: Rainwater tanks are increasingly adopted in Australia to reduce potable water demand and are perceived to reduce the volume of stormwater discharge from developments. This paper investigates the water balance of rainwater tanks, in particular the possible impacts these tanks could have in controlling the stormwater discharge volume. The study collected water quantity data from two sites in the Hawkesbury City Council area, New South Wales, Australia and utilised the collected data in a simple water balance mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…This is within the typical ranges of 0.8-0.95 for roof catchments used in similar studies [12,[25][26][27][28]. However, Van der Sterren et al [29] found out that a runoff coefficient of 0.9 tended to over-estimate the runoff from roof areas, hence the adoption of a runoff coefficient of 0.8 for this study. The roof area was varied in 5 increments from 20 to 200 m 2 .…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This is within the typical ranges of 0.8-0.95 for roof catchments used in similar studies [12,[25][26][27][28]. However, Van der Sterren et al [29] found out that a runoff coefficient of 0.9 tended to over-estimate the runoff from roof areas, hence the adoption of a runoff coefficient of 0.8 for this study. The roof area was varied in 5 increments from 20 to 200 m 2 .…”
supporting
confidence: 72%
“…This is within the typical ranges of 0.8-0.95 for roof catchments used in similar studies [12, 25-183 28] . However ,Van der Sterren et al, [29] found out that a runoff coefficient of 0.9 tended to over- Harvested runoff volume was estimated as:…”
mentioning
confidence: 99%
“…They carried out the financial viability analysis of the RWHS in single and multi-family buildings and found that in single-family households, an expected payback period would be between 33 and 43 years depending on the tank size, and for a multi-family, building a payback period would be as high as 61 years for a 20 m 3 tank. In Australian studies by van der Sterren et al [10][11][12], it was found that although RWHS would be very useful in providing required water in peri-urban regions of Sydney, water quality would not always meet the required standard in relation to heavy metals and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In remote regions, RWH contributes towards meeting one of the targets of Sustainable Development Goals (ensuring availability and sustainable management of water and sanitation for all). In urban areas, the rainwater harvesting (RWH) system is generally used as an alternative water supply means for the non-potable purposes (e.g., toilet flushing, laundry, irrigation and car washing), and for control of stormwater [3,4]. The RWH system is also used as a water source for small scale agricultural needs in both urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%